Spin dynamics simulations of collective excitations in magnetic liquids - Omelyan, I.P.; Mryglod, I.M.; Folk, R. (Condensed Matter Physics, 2000)
A novel approach is developed for computer simulation studies of dynamical properties of spin liquids. It is based on the Liouville operator formalism of Hamiltonian dynamics in conjunction with Suzuki-Trotter-like decompositions of exponential propagators. As a result, a whole set of symplectic time-reversible algorithms has been introduced for numerical integration of the equations of motion at the presence of both translational and spin degrees of freedom. It is shown that these algorithms can be used in actual simulations with much larger time steps than those inherent in standard predictor-corrector schemes. This has allowed one to perform direct quantitative measurements for spin-spin, spin-density and density-density dynamical structure factors of a Heisenberg ferroﬂuid model for the ﬁrst time. It was established that like pure liquids the density spectrum can be expressed in terms of heat and sound modes, whereas like spin lattices in the ferromagnetic phase there exists one primary spin in the shape of spin- spin dynamic structure factors describing the longitudinal and transverse spin ﬂuctuations. As it was predicted in our previous paper [Mryglod I., Folk R. et al., Physica A277 (2000) 389] we found also that a secondary wave peak appears additionally in the longitudinal spin-spin dynamic structure factor. The frequency position of this peak coincides entirely with that for a sound mode reﬂecting the effect of the liquid subsystem on spin dynamics. The possibility of longitudinal spin wave propagation in magnetic liquids at sound frequency can be considered as a new effect which has yet to be tested experimentally.